THE IMPACT OF LEADERSHIP AND WORK MOTIVATION ON THE PERFORMANCE OF NAGARI SUNGAI DUO OFFICIALS AS A STATISTICAL NAGARI IN DHARMASRAYA REGENCY - Febriansyach, Putra Sulung; Desna Aromatica; Hendri Koeswara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted with the aim of examining the influence of leadership and work motivation on the performance of employees in Nagari Sungai Duo, within the Nagari Statistik program in Dharmasraya Regency. The success of Nagari Statistik, which has become a digital-based one-data nagari, has made it easier for local governments to monitor and decide on policies to be implemented. This success would not have been possible without thorough planning and employee cohesion in supporting the innovation program. Therefore, leadership and motivation are crucial in improving employee performance. This research is based on the indicators of thought from A. Maslow, which focus on Leadership and Work Motivation in relation to Employee Performance. The research findings indicate that there is a strong influence between leadership and motivation on the performance of employees in Nagari Sungai Duo. This can be seen from the 32 respondents who participated as informants, showing their agreement with the statement that leadership and motivation have an impact on performance results. This is further supported by the fact that all variables of leadership and work motivation were found to be valid and reliable in relation to employee performance. Leadership had a t-value of 2.096, and Motivation had a t-value of 2.235 in relation to employee performance in the nagari apparatus. However, the researcher also observed that it is not only leadership and motivation that have an impact, but also work facilities. Since the Nagari Statistik program’s survey implementation was carried out by cadres who directly visited the community, the researcher believes that the available work facilities will also affect the performance results of employees in the execution of the Nagari Statistik program in Dharmasraya Regency.